Water Birth in the Hospital Setting. Issue 5 (October 2014) - Weaver, Melanie H.
Abstract Many women seek alternative birth methods, including water immersion for labor and birth, which several hospitals now offer. Although thousands of water births have occurred with few adverse outcomes documented, research findings on water birth have been sparce and mixed, and further study is necessary. Clinicians should discuss the potential risks and benefits of water birth and utilize informed decision‐making with women desiring this option. With careful selection and informed decision‐making, water birth should continue to be a choice for parents considering birth options. doi: 10.1111/1751–486X.12144